Checklist of the parasites of European eel Anguilla anguilla (Linnaeus, 1758) (Anguillidae) in Poland - Dzido, Joanna; Rolbiecki, Leszek; Izdebska, Joanna; Bednarek, Rafał (Biodiversity Data Journal, 2020)
The present paper lists all parasite species of the European eel Anguilla anguilla (Linnaeus, 1758), recorded in Poland, in both its saltwater and freshwater habitats. The list has been drawn up, based on data acquired since 1844. The majority of included parasite species are presented with fish infection parameters together with data on their developmental stages and occupied microhabitats, localities and dates of collection of the eels themselves. The database includes 62 parasite taxa (including 50 species, nine identified to the genus level and three to higher taxa), representing at least 47 genera and 39 families. The most frequently-noted parasites of the European eel are the cestode Bothriocephalus claviceps , the nematodes Anguillicoloides crassus , Camallanus lacustris and Raphidascaris acus and the acanthocephalan Acanthocephalus lucii . Four alien species have been noted from this host: A. crassus , the monogeneans Pseudodactylogyrus anguillae and Pseudodactylogyrus bini and the acanthocephalan Paratenuisentis ambiguus . The present list includes both new host records and earlier records not included in previous lists of parasites of eels.